Humeral shaft fractures treated by dynamic compression plates, Ender nails and interlocking nails - Chao, Ting-Cheng (Springer-Verlag, 2005)
Between January 1991 and December 2002, we treated 92 acute, displaced, closed humeral shaft fractures (AO classification type A). We used three fixation methods: dynamic compression plates (DCP) in 36 patients, Ender nails (EN) in 32 patients and interlocking nails (ILN) in 24 patients. The patients were followed for a minimum of 24 months. At one year, all fractures except two (one DCP/one ILN) had united. Patients treated with EN had shorter mean operation time, 51 (35–110) min; less mean blood loss, 70 (30–170) ml and shorter mean hospital stay, 5.8 (3–12) days. There were three iatrogenic radial nerve palsies: two in the DCP group and one in the ILN group. There was one wound infection. There were three cases with impingement of the shoulder but range of motion was restored after nail removal. For patients with multiple trauma or high operative risk, EN fixation served as a safer and faster procedure. ILN fixation offered a stable fixation via a smaller incision but more fracture comminution might happen.